Virtual reality and augmented reality displays: advances and future perspectives. (8th April 2021) - Yin, Kun; He, Ziqian; Xiong, Jianghao; Zou, Junyu; Li, Kun; Wu, Shin-Tson
Abstract: Virtual reality (VR) and augmented reality (AR) are revolutionizing the ways we perceive and interact with various types of digital information. These near-eye displays have attracted significant attention and efforts due to their ability to reconstruct the interactions between computer-generated images and the real world. With rapid advances in optical elements, display technologies, and digital processing, some VR and AR products are emerging. In this review paper, we start with a brief development history and then define the system requirements based on visual and wearable comfort. Afterward, various VR and AR display architectures are analyzed and evaluated case by case, including some of the latest research progress and future perspectives.